High-temperature-resistant heat-conducting interface material with POSS structure and preparation method thereof
By introducing POSS structure and modified thermal powder into the silicone thermal interface material, the problem of degradation of existing materials in high-temperature environments is solved, and the effect of efficient thermal conductivity and aging resistance is achieved.
Patent Information
- Application Number
- CN202411602414.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-04
AI Technical Summary
The performance of existing silicone thermal interface materials in high-temperature environments is deteriorated, the thermal conductivity drops sharply, the oil seepage is severe, and cracking occurs from time to time.
Using a high-temperature thermal conductivity interface material with a POSS structure, a modified thermal conductivity powder is prepared by combining cage-type silsesquioxane with vinyl silicone oil and other components, and a specific stirring and heating process is used to form a material with excellent heat resistance and thermal conductivity.
It achieves efficient thermal conductivity in high-temperature environments, avoids oil seepage and cracking problems, and significantly improves the aging resistance of the material.
Smart Images

Figure CN119552509A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of organic silicon thermal conductive interface materials, and in particular to a high temperature resistant thermal conductive interface material with a POSS structure and a preparation method thereof. Background Art
[0002] With the continuous development of natural science and the rapid progress of industrial technology, electronic devices are becoming more and more dense, functional and integrated, which brings great convenience to human information exchange, but problems are also coming one after another. One of the key technical difficulties is that electronic devices generate a lot of heat during operation. If the heat is not handled in time, it will affect the performance and stable operation of electronic devices. Therefore, efficient thermal management materials are extremely important for current electronic devices. At present, the research on efficient thermal conductive interface materials mainly starts from two aspects. The first aspect is to study the intrinsic thermal conductivity of polymers, specifically by synthesizing polymers with special structures to give them efficient thermal conductivity; the second aspect is to prepare thermally conductive composite materials, by adding thermally conductive fillers such as graphene, carbon nanotubes, boron nitride, silicon nitride, aluminum oxide, etc. to polymers, to construct effective thermal conductive paths, so that the polymers have the ability of efficient thermal conductivity. People prefer the second research idea in the study of thermal conductive materials, preparing thermally conductive composite materials.
[0003] At present, silicone materials are booming, and silicone thermal interface materials are emerging in an endless stream. Common silicone thermal interface materials include thermal mud, thermal gel, thermal pads, thermal grease, etc. Industrial application research has found that the performance of silicone thermal conductive materials deteriorates in high temperature environments, the thermal conductivity drops sharply, oil seepage is serious, and cracking occurs from time to time.
[0004] The structural formula of polyhedral cage oligomeric silsesquioxane is (RSiO)n, where n is 6, 8, 10, 12, etc. (named T6, T8, T10 and T12, etc. respectively), and the R substituent is an organic or inorganic group such as hydrogen, hydroxyl, phenyl, alkenyl, alkyl, aryl, alkenyl, halogen, or other derived more complex organic groups. From the structural point of view, cage silsesquioxane has two main characteristics: one is the closed or semi-closed cage structure composed of inorganic Si-O-Si chain segments, and the molecular size is between 1 and 3nm, which is a typical nano-sized material; the other is the Si-connected group R located at the top corner of the cube, and R can be an inorganic group or an organic group. In order to meet different needs, it can be designed to be derived into different groups. The inorganic cage skeleton structure gives POSS excellent inorganic properties. The organic molecular side chains are diverse, which increases the compatibility and reactivity of POSS with polymers. The organic / inorganic nanocomposite structure and performance of POSS are important factors for its wide application. When the R group is appropriate, POSS can be dispersed in the polymer at the molecular level, and the R group can also react with the reactive group in the polymer, so that POSS can be better mixed. In addition to being evenly mixed with the resin, POSS itself has a low dielectric constant, excellent heat resistance, flame retardancy, and much better processing performance than other inorganic fillers. These excellent properties and good compatibility with polymers make POSS widely used in traditional life fields and aerospace fields. Therefore, according to the current research results of POSS and industrial requirements, it is extremely important to provide a high temperature resistant thermal conductive interface material with a POSS structure. Summary of the invention
[0005] The present invention provides a high temperature resistant thermal conductive interface material with a POSS structure, comprising a component A and a component B. The component A comprises the following raw materials in percentage by mass: 2.0-8.2% of cage-type silsesquioxane, 4.5-15.2% of vinyl silicone oil, 0.1-0.2% of catalyst, and 80.0-91.0% of modified thermal conductive powder mixture; The B component includes the following raw materials in mass percentage: 3.0-4.8% of cage-type silsesquioxane, 3.1-13% of vinyl silicone oil, 0.001-0.02% of inhibitor, 80.0-94.0% of modified thermal conductive powder mixture, 0.5-5.0% of double-terminal hydrogen-containing silicone oil, and 0.2-2.5% of side chain hydrogen-containing silicone oil; The modified thermally conductive powder mixture is a mixture of modified thermally conductive powders of different particle sizes, and the modified thermally conductive powder is obtained by modifying thermally conductive powder with cage-type silsesquioxane.
[0006] The modified thermally conductive powder mixture is composed of modified thermally conductive powders with particle sizes of 0.5-1 μm, 2-5 μm, 10-20 μm and 30-60 μm mixed in a mass ratio of 1:2-5:5-12:7-18.
[0007] The cage silsesquioxane is a trisilanol phenyl cage silsesquioxane containing silanol and phenyl, and has the structural formula: , wherein R represents phenyl.
[0008] The vinyl silicone oil is a double-ended vinyl silicone oil with the structural formula: , where n1 ranges from 80 to 1000; The double-terminal hydrogen-containing silicone oil structural formula is: , where n2 ranges from 30 to 200; The side chain hydrogen-containing silicone oil structural formula is: , where n3 ranges from 5 to 20, and n4 ranges from 20 to 120.
[0009] The catalyst in the A component is KARSTEDT catalyst.
[0010] The inhibitor in the B component is one or a mixture of 3,7,11-trimethyldodecyne-3-ol, 2-propyn-1-ol, 3-methyl-1-dodecyne-3-ol or 1-ethynyl-1-cyclohexanol; The modified thermally conductive powder in the A component and the B component is one or more of zinc oxide, magnesium oxide, aluminum oxide, zirconium oxide, silicon nitride, aluminum nitride or silicon carbide modified by trisilanol phenyl cage silsesquioxane.
[0011] A method for preparing a high temperature resistant thermal conductive interface material having a POSS structure comprises the following steps: Preparation of component A: A1: Vinyl silicone oil and cage-type silsesquioxane are mixed, stirred and dispersed to obtain a mixture a1; A2: Add 2~5μm modified thermal conductive powder and 30~60μm modified thermal conductive powder to mixture a1, evacuate, heat, stir and disperse to obtain mixture a2; A3: Add 0.5~1μm modified thermal conductive powder and 10~20μm modified thermal conductive powder to mixture a2, evacuate, heat, stir and disperse to obtain mixture a3; A4: When the temperature of the mixture a3 is cooled to ≤40°C, the catalyst is added to the mixture a3, vacuumed, stirred and dispersed to obtain component A; Preparation of component B: B1: Vinyl silicone oil, cage-type silsesquioxane and double-terminal hydrogen silicone oil are mixed and stirred to obtain a mixture b1; B2: Add 2~5μm modified thermal conductive powder and 30~60μm modified thermal conductive powder to mixture b1, evacuate, heat, stir and disperse to obtain mixture b2; B3: Add 0.5~1μm modified thermal conductive powder and 10~20μm modified thermal conductive powder to mixture b2, evacuate, heat, stir and disperse to obtain mixture b3; B4: When the temperature of the mixture b3 is cooled to ≤40°C, the inhibitor and the side chain hydrogen-containing silicone oil are added to the mixture b3, vacuumed, stirred and dispersed to obtain component B; The A component and the B component are mixed to obtain a high temperature resistant thermal conductive interface material having a POSS structure.
[0012] The steps for preparing the modified thermally conductive powder are as follows: (1) Drying the thermally conductive powder to be modified for later use to obtain a dry thermally conductive powder; The cage-type silsesquioxane and ethanol are mixed and stirred to obtain a uniformly mixed modified solution; (2) Mixing the dried thermal conductive powder with the modified solution, heating and stirring to disperse; cooling to room temperature, vacuuming and stirring to disperse to obtain a coarse modified powder; (3) adding ethanol to the crude modified powder for washing, and then removing the ethanol to obtain an initial modified powder; (4) Evacuate the powder, heat, stir and disperse the initial modified powder to obtain a modified thermally conductive powder.
[0013] In step A1, the stirring speed is 90-120 r / min, the dispersing speed is 200-300 r / min; in step A2, the stirring speed is 130-160 r / min, the dispersing speed is 800-1000 r / min, and the vacuum degree is ≤-0.095 MPa; in step A3, the stirring speed is 130-160 r / min, the dispersing speed is 800-1000 r / min, and the vacuum degree is ≤-0.095 MPa; in step A4, the stirring speed is 90-120 r / min, the dispersing speed is 200-300 r / min, and the vacuum degree is ≤-0.095 MPa.
[0014] In step B1, the stirring speed is 90-120 r / min, the dispersion speed is 200-300 r / min; in step B2, the stirring speed is 130-160 r / min, the dispersion speed is 800-1000 r / min, and the vacuum degree is ≤-0.095 MPa; in step B3, the stirring speed is 130-160 r / min, the dispersion speed is 800-1000 r / min, and the vacuum degree is ≤-0.095 MPa; in step B4, the stirring speed is 90-120 r / min, the dispersion speed is 200-300 r / min, and the vacuum degree is ≤-0.095 MPa; Component A and component B are mixed in equal weight ratio.
[0015] The mass percentages of the raw materials for preparing the modified thermally conductive powder are as follows: thermally conductive powder 80-99.1%, cage-type silsesquioxane 0.87-10%, ethanol 0.03-10%; In step (2), the heating temperature is 90-130°C, the heating time is 2-4 hours, the stirring speed is 20-80 r / min, the dispersion speed is 120-200 r / min, and the vacuum degree is ≤-0.095 MPa; In step (4), the heating temperature is 40-50° C., the stirring speed is 20-80 r / min, the dispersion speed is 120-200 r / min, and the vacuum degree is ≤-0.095 MPa.
[0016] The beneficial effects of the present invention are as follows: (1) Powder modified by grafting of trisilanol phenyl cage silsesquioxane (POSS). Compared with other siloxane coupling agent modifications, trisilanol phenyl cage silsesquioxane (POSS) has a rigid silicon cage structure and excellent heat resistance. It can be used in high temperature environment without decomposition, giving the modified powder excellent aging resistance.
[0017] (2) Compared with other silicon-oxygen coupling agent modifications, the powder modified by grafting trisilanol phenyl cage silsesquioxane (POSS) achieves inorganic-organic hybridization at the molecular level, which is beneficial to the compatibility of the powder in silicone oil and reduces the interfacial thermal resistance.
[0018] (3) Trisilanol phenyl cage silsesquioxane (POSS) and silicone oil are mixed at the molecular level on the basis of physical blending. Compared with other physical blends, the POSS structure is introduced into the silicone oil matrix to form an anchor structure in the matrix, thereby inhibiting the slippage of the silicone oil molecular chain and helping to improve the heat resistance of the matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Temperature-thermal conductivity curves of the silicone thermal interface materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0020] The embodiments of the present invention will be described in detail below with reference to examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.
[0021] The silicone oil used in the following examples and comparative examples is specifically: Double-terminated vinyl silicone oil: , n1=600; Double-ended hydrogenated silicone oil: , n2=120; Side chain hydrogen silicone oil: , n3=14, n4=80.
[0022] Example 1 Preparation of modified alumina thermal conductive powder: (1) Weigh 1000 g of the alumina thermal conductive powder to be modified with particle sizes of 0.5 μm, 2 μm, 12 μm and 30 μm, respectively, and put them into an oven to dry for 4 hours for later use.
[0023] Mix 96.4 g of trisilanol phenyl cage silsesquioxane and 3.7 g of ethanol and stir evenly for 10 minutes to obtain a uniformly mixed modified solution; The four kinds of alumina thermal conductive powders with different particle sizes to be modified are placed into four planetary stirred reactors respectively. The planetary stirred reactors are numbered as follows: # Reactor, two # Reactor, three # Reactor, four # Reactor.
[0024] In one # Reactor, two # Reactor, three # Reactor, four # Add the modified solution to the reactor, add 10g of the modified solution, and then heat it for # Reactor, two # Reactor, three # Reactor, four # The reactor was heated to 120°C, stirred at 60r / min for 30min, and dispersed at 160r / min for 30min. The modification was carried out alternately by low-speed stirring and high-speed dispersion. The modification time was 2 hours in an environment of 120°C. Then it was cooled to room temperature, stirred and dispersed for 10min each under the condition of vacuum degree ≤-0.095MPa, with a stirring speed of 60r / min and a dispersion speed of 160r / min, to obtain four kinds of coarse modified alumina powders with different particle sizes.
[0025] 200 g of ethanol was added to the four kinds of coarse modified alumina powders with different particle sizes respectively, and the mixture was stirred at 100 r / min for 20 min to dissolve the unreacted trisilanol phenyl cage-type silsesquioxane in the ethanol, and then the ethanol was removed by suction to obtain four kinds of initial modified alumina powders with different particle sizes; The four types of initially modified alumina powders with different particle sizes were stirred and dispersed at a temperature of 50°C and a vacuum degree of ≤-0.095MPa for 30 minutes each, with a stirring speed of 60r / min and a dispersion speed of 180r / min to obtain four types of alumina modified thermal conductive powders with different particle sizes.
[0026] Preparation of component A: A1: Add 120.5 g of double-ended vinyl silicone oil and 25.0 g of trisilanol phenyl cage silsesquioxane (POSS) into a reactor, stir and disperse at a stirring speed of 100 r / min for 30 min, a dispersion speed of 200 r / min for 30 min, and a dispersion time of 30 min to obtain a mixture a1.
[0027] A2: Add 176.6 g of modified 2μm thermal conductive powder and 352.9 g of modified 30μm thermal conductive powder to mixture a1, heat, stir and disperse under vacuum degree ≤-0.095MPa, temperature 100°C, stirring speed 150r / min, stirring time 15min, dispersion speed 950r / min, dispersion time 15min, to obtain mixture a2.
[0028] A3: Add 44.5g of modified 0.5μm thermal conductive powder and 264g of modified 12μm thermal conductive powder to mixture a2, heat, stir and disperse under vacuum degree ≤-0.095MPa, temperature 100°C, stirring speed 150r / min, stirring time 20min, dispersion speed 950r / min, dispersion time 20min, to obtain mixture a3.
[0029] A4: When the temperature of the mixture a3 drops to 38°C, add 1.5 g of KARSTEDT catalyst to the mixture a3, stir and disperse under vacuum degree ≤-0.095 MPa, with a stirring speed of 100 r / min, a stirring time of 12 min, a dispersion speed of 260 r / min, and a dispersion time of 12 min to obtain component A.
[0030] Preparation of component B: B1: Add 130g of double-terminal vinyl silicone oil, 40.2g of trisilanol phenyl cage silsesquioxane and 20g of double-terminal hydrogen silicone oil into a reactor, stir and disperse at a stirring speed of 100r / min, a stirring time of 30min, a dispersion speed of 260r / min, and a dispersion time of 30min to obtain a mixture b1.
[0031] B2: Add 180.4g of modified 2μm thermal conductive powder and 360.5g of modified 30μm thermal conductive powder into mixture b1, heat, stir and disperse under vacuum degree ≤-0.095MPa, temperature 100°C, stirring speed 150r / min, stirring time 15min, dispersion speed 950r / min, dispersion time 15min, to obtain mixture b2.
[0032] B3: Add 50.5g of modified 0.5μm thermal conductive powder and 280.5g of modified 12μm thermal conductive powder into mixture b2, heat, stir and disperse under vacuum degree ≤-0.095MPa, temperature 100℃, stirring speed 150r / min, stirring time 20min, dispersion speed 950r / min, dispersion time 20min, to obtain mixture b3.
[0033] B4: When the temperature of the mixture b3 drops to 38°C, add 0.015 g of 1-ethynylcyclohexanol and 22.2 g of side-chain hydrogenated silicone oil to the mixture b3, stir and disperse under vacuum degree ≤-0.095 MPa, with a stirring speed of 100 r / min, a dispersion speed of 260 r / min, a stirring time of 12 min, and a dispersion time of 12 min to obtain component B.
[0034] 100 g of component A and component B were mixed, stirred for 30 min at a stirring speed of 100 r / min, and then cured in an oven at 80° C. for 10 min to obtain a high-temperature resistant thermal conductive interface material with a POSS structure.
[0035] Comparative Example 1 The difference from Example 1 is: (1) In the modification method of alumina thermal conductive powder, trisilanol phenyl cage silsesquioxane is replaced with octadecyltriethoxysilane; (2) POSS is not added when preparing components A and B; The rest is the same as in Example 1.
[0036] Example 2 The difference from Example 1 is: (1) When preparing modified alumina thermal conductive powders, the particle sizes of the four alumina thermal conductive powders are 0.6 μm, 3 μm, 15 μm and 35 μm; (2) When preparing components A and B, the particle size of the modified thermal conductive powder is changed from 2 μm to 3 μm, 30 μm to 35 μm, 0.5 μm to 0.6 μm, and 12 μm to 15 μm; The rest is the same as in Example 1.
[0037] Comparative Example 2 The difference from Example 2 is that: (1) In the modification method of alumina thermal conductive powder, trisilanol phenyl cage silsesquioxane is replaced with octadecyltriethoxysilane; (2) POSS is not added when preparing components A and B; The rest is the same as Example 2.
[0038] Example 3 The difference from Example 1 is: (1) When preparing modified alumina thermal conductive powders, the particle sizes of the four alumina thermal conductive powders are 0.8 μm, 3.5 μm, 16 μm and 40 μm; (2) When preparing components A and B, the particle size of the modified thermal conductive powder is changed from 2 μm to 3.5 μm, 30 μm to 40 μm, 0.5 μm to 0.8 μm, and 12 μm to 16 μm; The rest is the same as in Example 1.
[0039] Comparative Example 3 The difference from Example 3 is that: (1) In the modification method of alumina thermal conductive powder, trisilanol phenyl cage silsesquioxane is replaced with octadecyltriethoxysilane; (2) POSS is not added when preparing components A and B; The rest is the same as in Example 3.
[0040] Example 4 The difference from Example 1 is: (1) When preparing modified alumina thermal conductive powders, the particle sizes of the four alumina thermal conductive powders are 0.9 μm, 4.0 μm, 18 μm and 50 μm; (2) When preparing components A and B, the particle size of the modified thermal conductive powder is changed from 2 μm to 4 μm, 30 μm to 50 μm, 0.5 μm to 0.9 μm, and 12 μm to 18 μm; The rest is the same as in Example 1.
[0041] Comparative Example 4 The difference from Example 4 is: (1) In the modification method of alumina thermal conductive powder, trisilanol phenyl cage silsesquioxane is replaced with octadecyltriethoxysilane; (2) POSS is not added when preparing components A and B; The rest is the same as Example 4.
[0042] Example 5 The difference from Example 1 is: (1) When preparing modified alumina thermal conductive powders, the particle sizes of the four alumina thermal conductive powders are 1.0 μm, 5.0 μm, 20 μm and 55 μm; (2) When preparing components A and B, the particle size of the modified thermal conductive powder is changed from 2 μm to 5 μm, 30 μm to 55 μm, 0.5 μm to 1 μm, and 12 μm to 20 μm; The rest is the same as in Example 1.
[0043] Comparative Example 5 The difference from Example 5 is: (1) In the modification method of alumina thermal conductive powder, trisilanol phenyl cage silsesquioxane is replaced with octadecyltriethoxysilane; (2) POSS is not added when preparing components A and B; The rest is the same as Example 5.
[0044] The test results of thermal conductivity of the silicone thermal interface materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5 in different environments (test standard ASTM D5470, 80°C steady-state test method) are shown in Table 1 below: Table 1 Thermal conductivity (W / (m·K)) of the silicone thermal interface materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5 in different environments (120 min) 25℃ 80℃ 120℃ 160℃ 200℃ Double 85 (30 days) Example 1 3.5 3.5 3.5 3.4 3.3 3.5 Comparative Example 1 3.3 3.1 2.9 1.8 0.9 3.1 Example 2 3.7 3.7 3.6 3.6 3.4 3.7 Comparative Example 2 3.6 3.2 2.5 1.8 0.8 3.2 Example 3 3.7 3.6 3.6 3.5 3.3 3.6 Comparative Example 3 3.7 2.9 2.7 1.6 1.0 2.9 Example 4 3.6 3.5 3.5 3.2 3.1 3.5 Comparative Example 4 3.4 3.2 2.4 1.4 0.7 3.2 Example 5 3.8 3.8 3.7 3.5 3.3 3.8 Comparative Example 5 3.5 3.1 2.3 1.8 0.8 3.1 It can be seen from the data in the table that the organic silicon thermal interface materials prepared by using cage-type silsesquioxane-modified thermally conductive powders in Examples 1 to 5 have obvious high temperature resistance and aging resistance compared with the organic silicon thermal interface materials prepared in Comparative Examples 1 to 5.
Claims
1. A high temperature resistant thermal conductive interface material with a POSS structure, characterized in that: It includes component A and component B. The component A comprises the following raw materials in percentage by mass: 2.0-8.2% of cage-type silsesquioxane, 4.5-15.2% of vinyl silicone oil, 0.1-0.2% of catalyst, and 80.0-91.0% of modified thermal conductive powder mixture; The B component includes the following raw materials in mass percentage: 3.0-4.8% of cage-type silsesquioxane, 3.1-13% of vinyl silicone oil, 0.001-0.02% of inhibitor, 80.0-94.0% of modified thermal conductive powder mixture, 0.5-5.0% of double-terminal hydrogen-containing silicone oil, and 0.2-2.5% of side chain hydrogen-containing silicone oil; The modified thermally conductive powder mixture is a mixture of modified thermally conductive powders of different particle sizes, and the modified thermally conductive powder is obtained by modifying thermally conductive powder with cage-type silsesquioxane.
2. A high temperature resistant thermal conductive interface material with a POSS structure according to claim 1, characterized in that: The modified thermally conductive powder mixture is composed of modified thermally conductive powders with particle sizes of 0.5-1 μm, 2-5 μm, 10-20 μm and 30-60 μm mixed in a mass ratio of 1:2-5:5-12:7-18.
3. The high temperature resistant thermal conductive interface material with a POSS structure according to claim 1, characterized in that: The cage silsesquioxane is a trisilanol phenyl cage silsesquioxane containing silanol and phenyl, and has the structural formula: , wherein R represents phenyl.
4. The high temperature resistant thermal conductive interface material with a POSS structure according to claim 1, characterized in that: The vinyl silicone oil is a double-ended vinyl silicone oil, and its structural formula is: , where n1 ranges from 80 to 1000; The double-terminal hydrogen-containing silicone oil structural formula is: , where n2 ranges from 30 to 200; The side chain hydrogen-containing silicone oil structural formula is: , where n3 ranges from 5 to 20, and n4 ranges from 20 to 120.
5. The high temperature resistant thermal conductive interface material with a POSS structure according to claim 1, characterized in that: The catalyst in the A component is a KARSTEDT catalyst; The inhibitor in the B component is one or a mixture of 3,7,11-trimethyldodecyne-3-ol, 2-propyn-1-ol, 3-methyl-1-dodecyne-3-ol or 1-ethynyl-1-cyclohexanol; The modified thermally conductive powder in the A component and the B component is one or more of zinc oxide, magnesium oxide, aluminum oxide, zirconium oxide, silicon nitride, aluminum nitride or silicon carbide modified by trisilanol phenyl cage silsesquioxane.
6. A method for preparing a high temperature resistant thermally conductive interface material with a POSS structure according to any one of claims 1 to 5, characterized in that: The following steps are involved: Preparation of component A: A1: Vinyl silicone oil and cage-type silsesquioxane are mixed, stirred and dispersed to obtain a mixture a1; A2: Add 2~5μm modified thermal conductive powder and 30~60μm modified thermal conductive powder to mixture a1, evacuate, heat, stir and disperse to obtain mixture a2; A3: Add 0.5~1μm modified thermal conductive powder and 10~20μm modified thermal conductive powder to mixture a2, evacuate, heat, stir and disperse to obtain mixture a3; A4: When the temperature of the mixture a3 is cooled to ≤40°C, the catalyst is added to the mixture a3, vacuumed, stirred and dispersed to obtain component A; Preparation of component B: B1: Vinyl silicone oil, cage-type silsesquioxane and double-terminal hydrogen silicone oil are mixed and stirred to obtain a mixture b1; B2: Add 2~5μm modified thermal conductive powder and 30~60μm modified thermal conductive powder to mixture b1, evacuate, heat, stir and disperse to obtain mixture b2; B3: Add 0.5~1μm modified thermal conductive powder and 10~20μm modified thermal conductive powder to mixture b2, evacuate, heat, stir and disperse to obtain mixture b3; B4: When the temperature of the mixture b3 is cooled to ≤40°C, the inhibitor and the side chain hydrogen-containing silicone oil are added to the mixture b3, vacuumed, stirred and dispersed to obtain component B; The A component and the B component are mixed to obtain a high temperature resistant thermal conductive interface material having a POSS structure.
7. The method for preparing a high temperature resistant thermal conductive interface material having a POSS structure according to claim 6, characterized in that: The steps for preparing the modified thermally conductive powder are as follows: (1) Drying the thermally conductive powder to be modified for later use to obtain a dry thermally conductive powder; The cage-type silsesquioxane and ethanol are mixed and stirred to obtain a uniformly mixed modified solution; (2) Mixing the dried thermal conductive powder with the modified solution, heating and stirring to disperse; cooling to room temperature, vacuuming and stirring to disperse to obtain a coarse modified powder; (3) adding ethanol to the crude modified powder for washing, and then removing the ethanol to obtain an initial modified powder; (4) Evacuate the powder, heat, stir and disperse the initial modified powder to obtain a modified thermally conductive powder.
8. The method for preparing a high temperature resistant thermal conductive interface material having a POSS structure according to claim 6, characterized in that: In step A1, the stirring speed is 90-120 r / min, the dispersing speed is 200-300 r / min; in step A2, the stirring speed is 130-160 r / min, the dispersing speed is 800-1000 r / min, and the vacuum degree is ≤-0.095 MPa; in step A3, the stirring speed is 130-160 r / min, the dispersing speed is 800-1000 r / min, and the vacuum degree is ≤-0.095 MPa; In step A4, the stirring speed is 90-120 r / min, the dispersion speed is 200-300 r / min, and the vacuum degree is ≤-0.095 MPa.
9. The method for preparing a high temperature resistant thermal conductive interface material having a POSS structure according to claim 6, characterized in that: In step B1, the stirring speed is 90-120 r / min, and the dispersion speed is 200-300 r / min; in step B2, the stirring speed is 130-160 r / min, the dispersion speed is 800-1000 r / min, and the vacuum degree is ≤-0.095 MPa; In step B3, the stirring speed is 130-160 r / min, the dispersion speed is 800-1000 r / min, and the vacuum degree is ≤-0.095 MPa; in step B4, the stirring speed is 90-120 r / min, the dispersion speed is 200-300 r / min, and the vacuum degree is ≤-0.095 MPa; Component A and component B are mixed in equal weight ratio.
10. The method for preparing a high temperature resistant thermal conductive interface material having a POSS structure according to claim 7, characterized in that: The mass percentages of the raw materials for preparing the modified thermally conductive powder are as follows: thermally conductive powder 80-99.1%, cage-type silsesquioxane 0.87-10%, ethanol 0.03-10%; In step (2), the heating temperature is 90-130°C, the heating time is 2-4 hours, the stirring speed is 20-80 r / min, the dispersion speed is 120-200 r / min, and the vacuum degree is ≤-0.095 MPa; In step (4), the heating temperature is 40-50° C., the stirring speed is 20-80 r / min, the dispersion speed is 120-200 r / min, and the vacuum degree is ≤-0.095 MPa.
Citation Information
Patent Citations
Surface modification with polyhedral oligomeric silsesquioxanes silanols
CN101203378A
Low-thermal-resistance organic silicon heat conduction interface material and preparation method thereof
CN117210014A
Thermal interface material as well as preparation method and application thereof
CN118085295A
Octaaminophenyl POSS (Polyhedral Oligomeric Silsesquioxane) modified organic silicon thermal protection material and preparation method thereof
CN118085572A
Composite resin and preparation method thereof
CN118580641A